Report... to Commonwealth Heads of Government (Commonwealth Secretariat LondonGB, 1997)
Covers the Group's activities during the period December 1995 to September 1997. Focuses on three Commonwealth countries viz. The Gambia, Nigeria and Sierra Leone which have violated the principles contained in the Harare Declaration, assesses the nature of the infringement and recommends measures for collective Commonwealth action.
Additional copy located in the Office of the Secretary-General